Effect of forging pressure and rotational speed on the quality of rotary friction welding of Al 6063 and copper joints - Zulaida, Yeni Muriani; Anis, Muhammad; Al Huda, Mahfudz; Kirman, Kirman; Suhartono, Hermawan Agus (Mechanical Engineering for Society and Industry, 2026)
This study investigates the effect of forging/upset pressure and high rotational speed on the quality of dissimilar metal joints between aluminum 6063 (Al6063) and copper (Cu). The method uses solid-state rotary friction welding (RFW) method. Joining dissimilar metals poses challenges due to significant differences in thermal conductivity, melting point, and mechanical properties. At high rotational speeds, the increased heating rate and higher frictional pressure result in greater deformation of the aluminum component. A novel aspect of this research lies in its systematic evaluation of the combined effects of forging pressure and rotational speed in an area that has received limited attention in prior RFW studies. Despite not achieving full joint efficiency, the results demonstrate that increasing forging pressure significantly enhanced joint strength up to an optimum level. Consequently, higher rotational speeds led to larger and more irregular flash due to rapid heat generation. However, a well-balanced combination between pressure and speed produced stronger joints with less flash. Excessive pressure was found to widen flash formation, while the heat generation from high rotational speeds diminished after material deformation. The RFW process in this study reached temperatures approaching 300Â°C; a very few intermetallic phases were detected at the Al/Cu interface. These findings contribute valuable insights into improving the weldability and mechanical performance of dissimilar Al-Cu through parameter optimization in RFW parameters.